(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Proper mother posture during the second stage of labour, the most stressful time of delivery,is crucial for women to achieve a safe vaginal birth. During the second phase of labour, midwives play acrucial role in the control of maternal postures. Unfortunately, there isn’t a lot of data to back up claimsabout the best posture for the mother to be in during the second stage of labour. It’s also possible thatthe line between the various maternal roles is blurry. Women’s labour, maternal comfort and foetal andmaternal physiology are all affected by the posture the mother is in. This research set out to determinewhether or not there was a correlation between a mother’s posture during the second stage of labourand changes in maternal parameters and foetal heart rate in first-time mothers.